ผลของการอ่านหนังสือนอกเวลาที่มีต่อแรงจูงใจในการอ่านและการรับรู้ประสิทธิภาพในการอ่านของนักเรียนชั้นมัธยมศึกษาตอนต้น - สิทธิกูล ภูริชญ์; เอกโยคยะ มณีรัตน์ (An Online Journal of Education, 2015)
งานวิจัยนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาผลของการอ่านนอกเวลาที่มีต่อแรงจูงใจในการอ่านภาษาอังกฤษของนักเรียน 2) ศึกษาผลของการอ่านนอกเวลาที่มีต่อการรับรู้ความสามารถในการอ่านภาษาอังกฤษของนักเรียน หลังจากได้เข้าร่วมกิจกรรมการอ่านนอกเวลา โดยกลุ่มตัวอย่างเป็นนักเรียนในระดับชั้นมัธยมศึกษาตอนต้น โรงเรียนพระหฤทัย ดอนเมือง จำนวน 50 คน ซึ่งได้เข้าร่วมกิจกรรมการอ่านนอกเวลาเป็นระยะเวลาอย่างน้อยสองภาคการศึกษา การเก็บข้อมูลของงานวิจัยนี้ได้มาจากแบบสอบถามและการสัมภาษณ์ โดยการวิเคราะห์ข้อมูลเชิงปริมาณนี้ ใช้สถิติในรูปแบบพรรณนา การทดสอบค่าเอฟ การทดสอบค่าที และการทดสอบค่าสหสัมพันธ์แบบเพียร์สัน นอกจากนี้การวิเคราะห์ข้อมูลเชิงคุณภาพ ใช้การวิเคราะห์เนื้อหา ผลการวิจัยพบว่า 1) นักเรียนมีแรงจูงใจเพิ่มขึ้นในระดับสูงในการอ่านภาษาอังกฤษ เนื่องด้วยต้องการที่จะอ่านได้ดีขึ้นและต้องการเพิ่มพูนทักษะทางด้านการอ่านเขียน 2) นักเรียนมีการรับรู้ความสามารถของตนเองในทักษะการอ่านอยู่ในเกณฑ์ที่สูงขึ้น ซึ่งพบว่านักเรียนมีความรู้สึกที่ดีเมื่อได้อ่านบทความที่มีความยากได้สำเร็จลุล่วง และเชื่อว่ากิจกรรมการอ่านนอกเวลาช่วยพัฒนาทักษะและความสามารถทางด้านภาษาอังกฤษได้ การวิจัยนี้ยังแสดงค่าสหสัมพันธ์เชิงบวกระหว่างแรงจูงใจด้านการอ่านและการรับรู้ประสิทธิภาพด้านการอ่านอย่างมีนัยสำคัญทางสถิติที่ 0.05 The study aimed (1) to investigate the effects of extensive reading on students’ reading motivation, and (2) to examine students’ reading self-efficacy in English after participating in extensive reading activities. The participants of this study were 50 Thai students of lower secondary school at Praharuethai Donmuang School, who participated in ER activities for 2 semesters. The data collection was based on the information obtained from questionnaires and semi-structured interviews. The quantitative data was analyzed using descriptive statistics, f-Test, t-Test and Pearson’s correlation. The qualitative data obtained from semi-structured interviews was analyzed using content analysis The results showed that (1) the participants were highly motivated to read more in English since they wanted to be a better reader and wanted to develop their literacy skills and (2) students encountered high level of reading self-efficacy after they had participated in ER activities. They felt good when they were able to complete a difficult reading passage in English and they believed that ER activities can improve their reading abilities and skill. The study demonstrated positive correlation between reading motivation and reading self-efficacy inventory at 0.05 statistically significant level.